2006
DOI: 10.1177/0264550506060861
|View full text |Cite
|
Sign up to set email alerts
|

‘The worst tax form you’ve ever seen’? Probation officers’ views about OASys

Abstract: Classification with regard to their risk/needs has become an increasingly significant aspect of work with offenders generally. In England and Wales, the Offender Assessment System (OASys) used by the National Probation Service has a key role to play in effective practice. OASys is the latest in a series of such assessment tools, but despite considerable care taken over its development, users' views about its efficacy have not been explored. This article reports the results of the first national survey of Proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
(6 reference statements)
2
12
0
Order By: Relevance
“…Reflecting the experience of Mair et al (2006), who sought to interview a random sample of probation practitioners in the context of their research on OASys (the risk/needs assessment system used by probation and prison staff), we were not able to contact everyone we initially selected: it was relatively common to find that staff had left the service or moved to another post and in these cases another individual in the same team and/or a similar role was identified. However, the majority of those we approached agreed to take part: the small number who declined tended to cite lack of time or lack of knowledge about NOMS as their reason.…”
Section: The Areas and The Samplementioning
confidence: 99%
“…Reflecting the experience of Mair et al (2006), who sought to interview a random sample of probation practitioners in the context of their research on OASys (the risk/needs assessment system used by probation and prison staff), we were not able to contact everyone we initially selected: it was relatively common to find that staff had left the service or moved to another post and in these cases another individual in the same team and/or a similar role was identified. However, the majority of those we approached agreed to take part: the small number who declined tended to cite lack of time or lack of knowledge about NOMS as their reason.…”
Section: The Areas and The Samplementioning
confidence: 99%
“…Following this study, the Home Office in London started work on its own risk-need assessment system known as OASys (OASys Development Team 2001), which became the standard system throughout England and Wales by 2006. OASys was a complex and sophisticated instrument which aimed to produce an assessment of dangerousness or risk of harm in addition to a risk score for reconviction, but its introduction was slow and difficult: probation officers initially found it difficult and very time-consuming to use (Mair et al 2006) and the official evaluation reports concerning its accuracy and reliability remained unpublished for several years. When eventually published they showed that OASys could achieve a level of reliability in predicting reconviction which was comparable with LSI-R or very slightly better, but not quite as accurate as OGRS (Debidin 2009).…”
Section: The Introduction and Effects Of Risk Management Methodsmentioning
confidence: 99%
“…It emphasizes managerialism and punitiveness rather than improvements in services, and some of the developments reviewed in England and Wales have conformed more to this model than to the more optimistic account. The OASys risk assessment instrument, although performing at least as well as others in relation to accuracy, was often regarded as cumbersome and over-elaborate by practitioners (Mair et al 2006) and was imposed on them by managers rather than being seen by practitioners as a logical enhancement of what they were already trying to do. Generally it seems that innovations are more acceptable to practitioners if they can see how they add value to their practice, but in the very centralised management system which has existed in the National Probation Service of England and Wales since 2001 the tendency has been to try to manage change by very directive methods, with an increase in targets, regulations, procedures and form-filling which has greatly reduced the discretion and autonomy of individual staff.…”
Section: Critiquementioning
confidence: 99%
“…The tool consists of static measures, such as age or gender, and dynamic factors, for example family status or drug addictions. OASys has been extensively criticised in previous research for undermining probation officers in their independent professional risk assessments of offenders [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%